(untitled) (Bangladesh Journal of Medical Science, 2022)
Background: Asthma is a disease of the respiratory tract in the form of chronic inflammation. Chronic inflammation is one of them characterized by the remodeling of the airways mediated by the anti-inflammatory cytokine TGF-β. In addition there are also several immune cells that play a role such as macrophages, dendritic, neutrophils as producers of IL-12. The presence of the gut-lung axis allows the spread of inflammatory cytokines from the lungs to the intestines and vice versa. Lactobacillus brevis and Leuconostoc mesenteroides have the potential to modulate the immune system through its colonization of the gut. The study aimed to look at the effect of probiotics combined Lactobacillus brevis and Leuconostoc mesenteroides on the expression of TGF-β and IL-12 in the asthma model mouse ileum. Method: This experimental post-test only control group design study used 18 Sprague-Dawley mice. The mice were divided into 3 groups at random: control group (KI), asthma treatment (KII), asthma treatment with a combination of Lactobacillus brevis and Leuconostoc mesenteroides (KIII). Sensitization of asthma with OVA through intraperitoneal injection on days 0 and 14 and through inhalation on days 21 -63. Administration of combination probiotics per oral per day on days 21-63 after inhalation of OVA. The ileum network was taken on the 64th day and measured the expression of TGF-βand IL-12 with immunohistochemical methods and analyzed the percentage proportion of TGF-βand IL-12. Data analysis were conducted by One way ANOVA test and continued post hoc tests. Results: The percentage calculation of the proportion of TGF-βin thecontrol group (KI), asthma group (KII), and the combination group of L.brevis and L.mesenteroides (KIII) is 22.4 ± 15.27; 1.6 ± 2.12; 19.4 ± 6.65. While the percentage calculation of il-12 proportion in each group consecutively were 24.3 ± 19.67; 64.63 ± 9.90; 51 ± 16.62. One way ANOVA Test results on the percentage proportion of TGF-βhave a p value of 0.013 (p<0.05) which means there is a significant difference in the entire group. Furthermore, the Post Hoc Games-Howell test was conducted and obtained a p value of 0.003 (p<0.05) between the asthma group (KII) and the combination group of L.brevis and L.mesenteroides (KIII) which means there are significant differences between the two groups. One way ANOVA Test results on the percentage proportion of IL-12 have a p value of 0.011 (p<0.05) which means there is a significant difference in the entire group. Furthermore, the Post Hoc LSD test was conducted and obtained a p value of 0.001 (p<0.05) between the control group Post Hoc analyses was conducted and obtained a p value of 0.002 (p<0.05) with number of errors was 11.353 between the control group (KI) and asthma group (KII) which means there are significant differences between the two groups. Conclusion: The probiotic administration of lactobacillus brevis and Leuconostoc mesenteroides had no effect on the expression of TGF-β and had no effect on il-12 expression in the asthma model mouse ileum. It is necessary to do research on mice with asthma using combinations with other bacteria in order to get maximum effect. Bangladesh Journal of Medical Science Vol. 21(1) 2022 Page : 175-183